2022
DOI: 10.1177/15480518211067751
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Styles and Psychological Empowerment: A Meta-Analysis

Abstract: Psychological empowerment has become a popular construct in organizational research and practice. Leadership ranks high among the best predictors of employees’ psychological empowerment, yet little is known about which leadership styles prove more effective than others. This meta-analysis investigates the effects of four leadership styles on psychological empowerment. More specifically, we test whether empowering leadership evokes more psychological empowerment than transformational leadership, servant leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 146 publications
5
25
0
2
Order By: Relevance
“…Accordingly, Khan, Malik, and Saleem (2020) and Khan, Jaafar, et al (2020) have linked psychological empowerment and project success. We further point out that TL has been shown to be an antecedent to PE by Schermuly et al (2022) and Joo and Lim (2013). In our research, we expand on these conclusions by looking more closely at the factors involved in a study of public sector projects.…”
Section: Introductionmentioning
confidence: 57%
“…Accordingly, Khan, Malik, and Saleem (2020) and Khan, Jaafar, et al (2020) have linked psychological empowerment and project success. We further point out that TL has been shown to be an antecedent to PE by Schermuly et al (2022) and Joo and Lim (2013). In our research, we expand on these conclusions by looking more closely at the factors involved in a study of public sector projects.…”
Section: Introductionmentioning
confidence: 57%
“…Accordingly, when leaders articulate the organization's purpose and associated meaning, subordinates will experience their work as meaningful. Empirical research showed that transformational leadership, in particular, can increase subordinates’ experienced meaning at work (Grant, 2012; Schermuly et al., 2022).…”
Section: Leadership Factors Associated With Health and Well‐beingmentioning
confidence: 99%
“…However, psychological empowerment refers to nurses’ abilities to engage and feel congruence between their personal values and those of the organization ( Laschinger, Finegan, Shamian, & Wilk, 2001 ). Additionally, when nurses perceive that their work environment is providing them with opportunities to advance their career, they feel structurally and psychologically empowered ( Schermuly, et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%